Behavior of Steel Fiber-Reinforced Concrete Slabs Under Impact Loads - Trevor D Hrynyk; F Vecchio (ACI Structural Journal, 2014)
Seven intermediate-scale slabs were constructed and tested to failure under sequential drop-weight impacts. The slabs contained longitudinal reinforcing bars and were constructed with steel fiber contents ranging from zero (that is, conventional reinforced concrete) to 1.50% by volume. The data from the testing program were used to further assess the performance of steel fiber-reinforced concretes in impact-resistant applications and to provide a well-documented dataset pertaining to a research area which is currently limited within the literature. The test results showed that the addition of the steel fibers was effective in increasing slab capacity, reducing crack widths and spacings, and mitigating local damage under impact. Although the slabs in the program were designed to be flexure-critical under static loading conditions, the development of inertial forces under impact loading conditions led to observed responses and failure modes that were governed by shear.